The Impact of Marine Human Engin The Impact of Marine Human Engineering on Organizational Development: An Exploratory Study in the Iraqi Maritime Sector: The Impact of Marine Human Engineering on Organizational Development: An Exploratory Study in the Iraqi Maritime Sector - Al-Nour, Hussein; Saleh, Prof. Dr. Rasha (The Gulf Economist, 2025)
The current study aimed, within its theoretical and field framework, to test the relationship and impact of maritime human engineering with its dimensions (professional work environment, risk control and prevention, education and training, occupational health and safety management) on organizational development with its dimensions (evaluation, organizational, organizational intervention, organizational sustainability). In order to achieve the study objectives, the researcher built a hypothetical model to interpret the nature of the relationship between the independent variable (maritime human engineering) and the dependent variable (organizational development). The survey method was adopted, targeting the community and sample of the study in the Iraqi maritime sector, including senior and middle management in maritime sectors, with an actual sample size of (205). Data was collected using a questionnaire tool, and statistical analysis software (AMOS, V.24) and (SPSS, V.26) were used. The results showed a relationship and impact of the independent variable maritime human engineering on the dependent variable organizational development. The study presented a number of recommendations, the most important of which was the establishment of a department or section for human engineering in all companies operating in the Iraqi maritime sector and sending their employees to external courses to master this important specialization that is not currently activated in the maritime field.